Digitalisasi Material Manifest untuk Meningkatkan Efisiensi Administrasi Logistik di PT Duta Marine - Ameliya Cantik Maulani; Refiana Dwi Maghfiroh (Nirta Learning Centre, 2026)
Abstract. This study examines the improvement in administrative efficiency resulting from the digitalization of material manifest documents at PT Duta Marine. The initial issue identified during the internship was the use of offline files, which were inefficient, difficult to revise, and limited collaboration among administrative staff. This study aims to evaluate the effectiveness of transitioning from offline document management to an online spreadsheet system that enables real-time editing and centralized data storage. A qualitative descriptive approach was employed through direct observation, informal interviews with administrative staff, and document analysis to compare offline and online manifest formats. The findings indicate that the digital system significantly reduces revision time, minimizes data duplication, improves data accuracy, and enhances document accessibility for relevant users. Therefore, the digitalization of material manifests using an online spreadsheet platform is recommended as an effective approach to improving administrative efficiency, strengthening inter-staff coordination, and supporting transparency in document control within logistics operations at PT Duta Marine. Keywords: administrative efficiency, digitalization, document management, material manifest, spreadsheet system.